Senses of Echo Lake: Michael Palmer, Stanley Cavell, and the Moods of an American Philosophical Tradition - Richard Deming (Humanities, 2019)
This essay explores a philosophical tradition that Stanley Cavell has traced out and which he emphasizes as being American inasmuch as it is arises out of the thinking of Ralph Waldo Emerson and Henry David Thoreau. It then investigates how the poems of the avant-garde poet Michael Palmer link with, overlap with, this strain of American philosophy in terms of how it enacts an understanding of what we might call “philosophical mood,” on outlook based on the navigation of representation, generative self-consciousness, and doubt that amounts to a form of epistemology. The essay does not trace the influence—direct or otherwise of Cavell and his arguments for philosophy on the poems, despite a biographical connection between Cavell and Palmer, his former student. Instead it brings out the way that one might fruitfully locate Palmer’s work within an American literary/philosophical continuum. The article shows how that context opens up the work to a range of important existential and ethical implications. I endeavor to show that Notes for Echo Lake, Palmer’s most important collection, locates itself, its language, within such a frame so as to provide a place for readerly encounters with the limitations of language. These encounters then are presented as an opportunity for a deeper understanding of subjectivity and for attuning oneself to the role that active reading and interpretation might play in moral perfectionism.